2016
DOI: 10.1002/cmdc.201600095
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Resistance Relationships: Interrogating Antiseptic Resistance in Bacteria with Multicationic Quaternary Ammonium Dyes

Abstract: Bacterial resistance toward commonly used biocides is a widespread yet underappreciated problem, one which needs not only a deeper understanding of the mechanisms by which resistance proliferates, but also means for mitigation. To advance our understanding of this issue, we recognized a polyaromatic structural core analogous to activators of QacR, a negative transcriptional regulator of the efflux pump QacA, and envisioned a series of quaternary ammonium compounds (QACs) based on this motif. Using commercially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
38
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 16 publications
4
38
1
5
Order By: Relevance
“…[13] Our own work initially pushed towards the inclusion of multiple (up to 4) cationic groups, [14] although subsequent data indicated the diminishing advantages of cations beyond the first two. [15] We have thus pivoted to eye molecular geometry, [8a] based on the logic that both cationic presentation to the net anionic bacterial cell membrane is important for Coulombic attachment, and that non-polar groups must subsequently intercalate into the bacterial membrane to trigger disruption.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[13] Our own work initially pushed towards the inclusion of multiple (up to 4) cationic groups, [14] although subsequent data indicated the diminishing advantages of cations beyond the first two. [15] We have thus pivoted to eye molecular geometry, [8a] based on the logic that both cationic presentation to the net anionic bacterial cell membrane is important for Coulombic attachment, and that non-polar groups must subsequently intercalate into the bacterial membrane to trigger disruption.…”
mentioning
confidence: 99%
“…Having previously observed both the facile installation of amide-containing non-polar moieties, [15a,19b] as well as their impressive bioactivity, we chose to prepare an analogous set of piperazine bisQACs incorporating the amide functionality on the side chain. We also suspected that the amide functional group might lend itself towards a “kink” in the side chain, allowing for a less linear non-polar extension from our core structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10,11] Still others have focused on the designo f" soft" amphiphiles, which incorporateh ydrolyzable bondst hat may decrease toxicity due to their ability to be readily metabolized. [12][13][14] Such QACs typicallyd isplay equipotent activity to their non-hydrolyzable counterparts, while degradinga fter af ew hours to af ew days.O ur laboratories have likewise endeavored to advance our QACc apacities, investigating av ariety of bis-and multiQAC structures; [15][16][17][18][19][20] ar eview of our efforts has recently been reported. [21] Common themes have emerged-optimal alkyl chain lengths are generally~12 carbons, and the incorporation of at least two ammonium cations generally leads to an increase in antimicrobiala ctivity,a s well as significant biofilm eradication capability.MultiQACs also show the promise to address bacterial resistance;whereas bacteria bearing genes for key efflux pumps show increased tolerance toward many commerciallya vailable QACs, resistantb acteria are seemingly thwarted in mostc ases by multicationic systems.…”
mentioning
confidence: 99%
“…Previous studies of bacterial susceptibilityt oQ ACs suggested that the presence of efflux pumps is as trong protective factor,e ven stronger perhaps than the presence of as econd bacterialm embrane as in Gram-negative strains. [20] QACs that do not trigger bacterial resistance, namely qac-encoded efflux pumps,a re thus more efficacious. We hypothesized that an extended cationic surface (wherein charges were spread over al arger surfacea rea) would greatly decrease diffusion into bacterialc ells, thus minimizing resistance and promoting efficacy.F urthermore, we postulated that these scaffolds might also have increased selectivity against prokaryotic cells based on their phospholipid composition in comparison with their eukaryotic counterparts.…”
mentioning
confidence: 99%